Response of microplankton size structure to summer stratification, freshwater influx and coastal upwelling in the Southeastern Arabian Sea. (15th January 2020) - Karnan, C.; Jyothibabu, R.; Arunpandi, N.; Albin, K. Jose; Parthasarathi, S.; Santhi Krishnan, S.
Abstract: A year-round FlowCAM-based study of micro-plankton (20–200 μm) size structure was conducted in several locations along a cross-shore transect off Kochi in the near-shore waters of the southeastern Arabian Sea (SEAS; along the southwest coast of India). The study area was characterized by a warmer and thermally stratified water column during the Pre-Southwest Monsoon (PSWM; March to May), which was replaced by the cool and hypoxic upwelled waters at the sub-surface and low salinity estuarine waters at the surface during the Southwest Monsoon (SWM; June to September). Irrespective of seasons, micro-autotrophs displayed higher abundance and biomass closer to the coast as compared to the offshore locations. The seasonal trend in the abundance and biomass of micro-autotrophs mismatched in the study region, the former was the highest (av. 8430 ± 2927 ind/L and av. 10.3 ± 2 μgC/L) during the PSWM and the latter during the SWM (av. 7703 ± 1237 and av. 16.8 ± 3.5 μgC/L). Micro-autotroph biomass was found to be higher in the surface waters, with an exception during the SWM, when larger micro-autotrophs (av. 137184 ± 10196 μm³/ind.) were observed in the subsurface. The highest seasonal abundance of micro-autotrophs (av. 8430 ± 2927 ind/L) during the PSWM could be attributed to the presence of smaller individuals (biovolume av. 59801 ± 6906 μm³/ind.). The overall spatial distribution of micro-heterotrophs was similar to that of the micro-autotrophs, with their high abundance and biomass in locations closer to the coast. Also, their abundance was found to be higher throughout the water column during PSWM, while it decreased noticeably in the deeper waters during the rest of the period. During the SWM, low PAR, high nutrients and high salinity in the sub-surface waters facilitated the dominance of larger micro-autotrophs (diatoms) such as Fragilaria (av. 211093 ± 8431 μm³/ind.) and Thalassiosira (av.80027 ± 5031 μm³/ind), whereas low salinity and high nutrient water mass from the adjacent Cochin (Kochi) backwaters favored high abundance of smaller micro-autotrophs such as Thalassionema (av. 17220 ± 756 μm³/ind.) and Skeletonema (av. 11831 ± 533 μm³/ind.) in the surface water. This study evidences for the first time that due to temporal changes in water masses in the near-shore waters in the SEAS, there are considerable seasonal and spatial variations in the size structure and composition even within the micro-plankton community itself. Highlights: Deals with ecology of plankton size structure in the inshore waters along the southwest coast of India. Elucidated how freshwater influx and upwelling influence autotrophic community size structure. Capping effect of low saline water mass on upwelled water mass in the subsurface facilitated different plankton communities. Low saline waters facilitated smaller autotrophs, whereas, upwelled waters the larger autotrophs.